Inclusions in elasto-plastic solids under the influence of internal and external pressures - Tapan Kumar Das; P. R. Sengupta; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
An attempt is made to study the problems of spherical and circular inclusions in elasto-plastic solids under the action of internal increasing pressure and external constant pressure, taking into consideration of the work-hardening effect. Particular attention is given to the linear work hardening effect on both problems. It is shown that results of this analysis are in good agreement with those of ideal plastic solids.